The limits of agency theory in the law of franchising - Mohd Ishan, Zahira; S. M. Hussain, Shaik Mohd Noor Alam (2008)
This paper aims to point the limits of using agency theory in issues relating to franchising despite franchising being developed from a hybrid body of laws including agency. It applies the qualitative approach by means of inductive reasoning using the historical research method. Franchising as a business method is a unique and relatively new area of commercial law. The elements of franchisors’ controls, however, lead to the debates of whether franchisors are principals to their franchisees and whether their relationship is fiduciary in nature or at an arm’s length. The former issue is common in a third party claim on franchisor’s liability over the act done by his franchisee. The latter issue is common in the day-to-day relationship of the franchisor and his franchisees. The solutions for these issues, however, should not lie on the agency theory but to the law of franchising of its own.